Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry for the identification of beta-hemolytic streptococci - Zhou, Chunmei; Tao, Lili; Hu, Bijie; Ma, Jian; Ye, Xiangru; Huang, Shenglei; Ma, Yan; Shan, Yuzhang (Journal of Thoracic Disease; Vol 7, No 4 (April 28, 2015): Journal of Thoracic Disease, 2015)
Objective: Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) has emerged as promising technology for species identification. The purpose of this investigation was to compare the performance of MS and the traditional method for identification of beta-hemolytic streptococci (BHS). Methods: Clinical BHS isolates were identified by the BD Phoenix SMIC/ID Streptococcal panels, and two MALDI-TOF MS platforms: the VITEK MS and the Bruker MALDI Biotyper systems respectively. In case of discordant results, 16sRNA sequencing was performed to provide the reference ID. Results: A total of 96 isolates of BHS were analyzed. Thirty-six isolates (20.8%) were re-tested by BD Phoenix for identification failure; and four isolates (4.2%) were rerun on the Bruker system for low identification score. No isolate need a second run for identification by Vitek MS system. Overall, BD Phoenix, BioTyper and Vitek MS automated system accurately identified 76 strains (79.2%), 91 (94.7%) strains and 92 (95.8%) strains, respectively. Conclusions: Our study suggests that MALDI-TOF MS is a superior method to conventional phenotypic methods for BHS identification.